2010
DOI: 10.1021/jp1098975
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Zeolite Beta in OSDA-Free, Seed-Assisted Synthesis

Abstract: Recent reports on the organic structure-directing agent (OSDA)-free synthesis of some zeolites with the aid of seed crystals have opened a new way to the robust and environmentally friendly production of industrially valuable zeolites. However, the details on the crystallization behavior as well as the role of the seeds have not been fully clarified yet. In this study, the crystallization process of zeolite beta in the OSDA-free, seed-embedded Na+−aluminosilicate gel system, which never yields beta in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
150
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 40 publications
3
150
0
7
Order By: Relevance
“…44 Authors showed further that it is possible to synthesize zeolites using seeds of other topology, which have common building units. The mechanisms proposed by Xiao et al 21,43 and Okubo et al 20 for the SDA-free synthesis of zeolites, in principle, hold well for this work . However, considering the very small amount of seeds used for zeolite synthesis in this work, we tentatively suggest that dissolution of seeds proceeds to much smaller aggregates in comparison to previously mentioned works, giving rise to nuclei which act as a core to build new zeolite crystals.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…44 Authors showed further that it is possible to synthesize zeolites using seeds of other topology, which have common building units. The mechanisms proposed by Xiao et al 21,43 and Okubo et al 20 for the SDA-free synthesis of zeolites, in principle, hold well for this work . However, considering the very small amount of seeds used for zeolite synthesis in this work, we tentatively suggest that dissolution of seeds proceeds to much smaller aggregates in comparison to previously mentioned works, giving rise to nuclei which act as a core to build new zeolite crystals.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Yu et al 19 reported ultrafast synthesis of SAPO-34 in the presence of seeds in 10 min. The faster formation of products is attributed to the fact that addition of seeds suppresses the necessity of a nucleation step either by partial dissolution of seeds to provide growth surface for new crystals 20 or via a core-shell growth mechanism. 21 Naturally, fast crystal growth might lead to the formation of some framework imperfections, which in turn can affect physical and chemical (read as catalytic) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Majano et al also reported seeded synthesis of Beta zeolite by the use of a little Beta nanocrystals containing small amount of organic template in the absence of additional organic templates [37]. Subsequently, Kamimura et al demonstrated the effects of initial gel composition, quantity of seed crystals, and crystallinity of the seeds, as well as the Si/Al ratios on the crystallization behavior of the Beta phase [38,39]. Xie et al have demonstrated the core-shell structure mechanism on the formation of Beta zeolite from seeds-directed synthesis (Beta-SDS) [40].…”
Section: Introductionmentioning
confidence: 99%
“…High-silica ferrierite, with Si/Al ratio close to 15, was first synthesized in OSDA-free conditions using CDO crystals as seeding [209]. Mordenite is an important catalyst in several petrochemical processes (such as hydrocracking, reforming, alkylation, among other), Reproduced from [207].…”
Section: Direct Synthesis Of Osda-free Zeolitesmentioning
confidence: 99%
“…Interestingly, nucleation and crystallization mechanisms on OSDA-free conditions in the presence of zeolite seeds were studied in detail by these researchers. OSDA-free beta zeolite was first selected as the model case for the study [207]. From detailed characterization measurements, Okubo et al proposed a mechanism based on different steps for the crystallization of OSDA-free beta material (see scheme in Figure 14).…”
Section: Direct Synthesis Of Osda-free Zeolitesmentioning
confidence: 99%